ANALISIS MANAJEMEN DAN KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN DI SD ISLAM TERPADU LHI - Siti Nofiati, S.Pd (Jurnal Riset Daerah, 2024)
This research aims to 1) analyze the implementation of leadership management by female school principals at the LHI Banguntapan Integrated Islamic Elementary School, 2)analyze the inhibiting and supporting factors in implementing leadership management of female principals at the LHI Banguntapan Integrated Islamic Elementary School, 3)analyze the expected development needs to support the leadership management of female principals at LHI Banguntapan Integrated Islamic Elementary School. This research uses qualitative methods with interview, observation and documentation data collection techniques. There were six research subjects including the principal, deputy principal, teachers and school committee. Data analysis for this research is the Miles and Hubberman data model which consists of data reduction, data display and conclusions. The validity of this research uses triangulation techniques and member checks. The results of this research show that the implementation of leadership management by female principals at the LHI Banguntapan Integrated Islamic Elementary School is very good. The school principal has good leadership skills and uses a facilitative leadership pattern. Supporting factors for school principals are the high enthusiasm for learning possessed by the principal, young employee teachers so that they are enthusiastic about increasing their own capacity, financial support, support for infrastructure and support from parents. Inhibiting factors are limited time and the conditions of parents who have various backgrounds. The development need that is expected to support the leadership management of female principals at LHI Banguntapan Integrated Islamic Elementary School is increasing personal capacity in the area of English language skills. The principal of the LHI Banguntapan Integrated Islamic Elementary School has various abilities that support the principal's leadership management.